(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
In this study, a sinusoidal PWM rectifier is designed and modeled to enhance the performance of the system under different operating conditions. The system is tested under balanced AC sources and various loads. It is also tested under unbalanced and distorted three-phase AC sources. The key performance goal of the suggested system is to minimize the total harmonic distortion (THD) of the supply AC current while maintaining a unity power factor. The proposed controller is designed to drive the IGBTs and generate the required output DC voltage with minimal THD and a power factor of unity. The designed system and controller were simulated, and the obtained results demonstrate good power quality. The system showed decreased THD and a unity power factor across various loads, as well as under stable and unstable conditions in both steady-state and transient conditions. The maximum THD value is 3.8992% at 600Vdc, while the minimum THD value is 0.3867% at 1200Vdc. These values are achieved with an almost unity power factor under all conditions. These results demonstrate the effectiveness of the proposed system in dynamic operations.